Blocking performance of extended pruned vertically stacked optical banyan structure under different link failure conditions - Sabrina Alam; Fahmida Sharmin Jui (Universitas Ahmad Dahlan, 2021)
The blocking performance of extended pruned vertically stacked optical banyan (VSOB) networks under different link failure conditions has been analyzed in this paper. We applied plane fixed routing with linear search and plane fixed routing with random search algorithms to route the optical data through the network in our simulation. Our simulation results show that adding one or two extra planes to the pruned VSOB network reduces the blocking probability significantly. Beyond two extra planes, the decrease of blocking probability is not so significant. A close approximation of the minimum number of planes required to make the extended pruned vertically stacked optical banyan networks nonblocking has been presented.